﻿New species of awl-head katydids, Cestrophorus and Acanthacara, from the Andes of Ecuador (Orthoptera, Conocephalinae, Cestrophorini) - Holger Braun; Glenn K. Morris (Journal of Orthoptera Research, 2022)
The Cestrophorini are small katydids of Ecuador’s montane rainforest bearing a prominent awl-shaped fastigium verticis. They are unusual among Conocephalinae in lacking pre-tympanic ear chambers: their eardrums are exposed on their fore tibiae. There are presently two genera, Cestrophorus Redtenbacher, 1891 and Acanthacara Scudder, 1869. Awl-head habitat includes both climax forest and anthropogenically disturbed areas (e.g., pastures, roadsides) on lower slopes in the drainage of the volcanoes Aliso, Chiles and Tungurahua. At night, males perch on low vegetation and stridulate to attract females. To three extant species, we add a further seven, two in Cestrophorus and five in Acanthacara. Male calling songs were recorded and analyzed for all three Cestrophorus species and for three of the Acanthacara spp. We describe and discuss the waveforms of their sinusoid and transient sound pulses in time and frequency domains.